EU Climate Policy Up to 2020: An Economic Impact Assessment - Andreas Löschel; Christoph Böhringer; Ulf Moslener; Thomas F. Rutherford (Verein für Socialpolitik, 2010)
In its fight against climate change the EU is committed to reducing its overall greenhouse gas emissions to at least 20% below 1990 levels by 2020. To meet this commitment, the EU builds on segmented market regulation with an EU-wide cap-and-trade system for emissions from energy-intensive installations (ETS sectors) and additional measures by each EU Member State covering emission sources outside the cap-and-trade system (the non-ETS sector). Furthermore, the EU has launched additional policy measures such as renewable energy subsidies in order to promote compliance with the climate policy target. Basic economic reasoning suggests that emission market segmentation and overlapping regulation can create substantial excess costs if we focus only on the climate policy target. In this paper, we evaluate the economic impacts of EU climate policy based on numerical simulations with a computable general equilibrium model of international trade and energy use. Our results highlight the importance of initial market distortions and imperfections as well as alternative baseline projections for the appropriate assessment of EU compliance cost.
Keywords: D58; Q48; Q54; 330; climate policy; market distortions; baseline projections; computable general equilibrium